New Method to Calculate the Angular Weighting Function for a Scattering Instrument: Application to a Dust Sensor on Mars - David Santalices; Antonio J. de Castro; Susana Briz (Sensors, 2022)
Suspended dust above the Martian surface is an important element in Martian climatology. In the frame of the Exomars’22 mission, we developed a dust sensor instrument, designed to provide size parameters of dust particles suspended in Mars surface from the light scattered by the particles. Thus, to interpret the data of the dust sensor, we need a method to calculate the theoretical optical power dispersed by the particles and, therefore, the theoretical signal obtained by the instrument. This signal depends on the suspended particles and on the instrument configuration. In this paper, we present a new method to calculate the angular weighting function (<semantics>Wf</semantics>) for scattering sensors. <semantics>Wf</semantics> encompasses the scattering angles measured by the sensor and depends only on the instrument and not on the suspended particles. To calculate this <semantics>Wf</semantics>, we use fundamental radiometry principles and an appropriate coordinate system, where one coordinate is the scattering angle. The method is applied to the dust sensor instrument and compared with other methods. The comparison highlights the advantages of the proposed method since it avoids using an ideal sampling volume, preserves the radiometric meaning, and avoids instrument calibration. The effectiveness of the method makes it a valuable tool for the design of scattering instruments and also for the interpretation of their data.